CALLIGRAPHIC TRADITIONS IN CULTURE AND EEUCATION OF MODERN CHINA - E. M. Kulanina (Концепт: философия, религия, культура, 2019)
Modern processes among Chinese citizens in the field of studying history of their culture convincingly demonstrate an increasing consistent interest in such an important part of it as writing and calligraphy traditions. After detailed analysis of the fundamental documents that control returning calligraphy to the basic school curriculum, it is possible to point out a strong tendency in sustained government support for calligraphy-based courses both as compulsory or additional education. University education also includes calligraphy. Currently, the Government of China is carrying out an educational reform focusing on teaching calligraphy in primary and secondary education; well-qualified teachers are being trained for carrying out this reform. Also there is another arousing interest in teaching calligraphy skills for the aged, which accords with the general direction of social work with a “culture of age” represented by Chinese traditions. The population interest in calligraphy is supported by the cultural-educational activities of numerous calligraphic associations.The recent discussions on calligraphy training demonstrate that this type of activity is not inferior to the pressure of digital technologies, but on the contrary, demonstrate that it still remains as a mean of communication between people, is used by government as another mean for increasing cultural level of the population, for preserving and increasing national cultural heritage.The methodology of studying mentioned questions is based on a content analysis of Chinese media publications, as well as the fundamental documents that are provided for public access on official websites of the Ministry of Education of the People’s Republic of China and on the university websites which implement and develop the latest strategy in calligraphy teacher training program. The main result of the study could be considered as clarifying the role of calligraphy in modern Chinese culture, where an intentional return to this method of mastering traditions is associated with the desire to incorporate the best of the previous achievements, and combine it with the desire to withstand the negative consequences of the changed living rhythm of modern society.